Therapeutic Plasma Exchange In Septic Shock Patients: A Scoping Review of Clinical Evidence (2015-2024) - Saparingga Dasti Putri; Ayu Prawesti Priambodo; Natalia Tambunan; Sultan Muhammad Wahyu Pamungkas (Jurnal Keperawatan Galuh, 2026)
Septic shock is a critical condition with high mortality caused by systemic inflammatory responses and multiple organ dysfunction. Therapeutic Plasma Exchange (TPE) has been proposed as an adjunctive therapy to eliminate inflammatory mediators and restore vascular homeostasis. This study aimed to map and synthesize clinical evidence on the use of TPE in patients with septic shock. A scoping review design was employed based on the Arksey and O’Malley framework, with reporting guided by PRISMA-ScR. Literature searches were conducted in PubMed, ScienceDirect, Sage Journals, and Springer Nature for English-language articles published between 2015 and 2024. A total of 12 studies met the inclusion criteria and were analyzed thematically. The results indicated that TPE was associated with improvements in hemodynamic parameters, modulation of inflammatory responses, endothelial protection, coagulation regulation, increased immunoglobulin levels, and reduced short-term mortality in several studies. However, the strength of evidence remains limited due to heterogeneity in study design, small sample sizes, and protocol variability. TPE shows potential as an adjunctive therapy, but large-scale randomized trials are needed before widespread recommendation.